Peralatan Pemboran Dan Produksi : Hoisting System Equipment (Kajian Literature Review Pada Pembelajaran Praktikum) - Ritchad Steven Partogi Hasugian; Rachmasari Pramita Wardhani; Guis Pangeran Lemuyaq; Rendy Prasetiyo Garanta; Farhan Naufal Jufri (JURNAL TEKNOSAINS KODEPENA, 2025)
The hoisting system equipment course aims to provide participants with an indepth understanding of the operating principles, components, and safety aspects of hoisting equipment in the oil and gas, construction, and manufacturing industries. Through practical learning, students will gain a comprehensive understanding of the components, functions, and operating principles of hoisting systems. The importance of hoisting system knowledge in oil and gas drilling is that participants become familiar with the main components of hoisting system equipment, the function of each component, and the operating principles of hoisting systems in field operations. The type of research used in this practicum is classroom action research. The implementation phase includes preparing tools and materials, introducing and understanding the object, conducting observations and making rough sketches, and creating narratives based on direct observations and literature review. By studying the operating principles ofhoisting systems, students gain a clear understanding of their crucial role in the oil and gas drilling industry and the construction sector.